2019
DOI: 10.1021/acschemneuro.9b00503
|View full text |Cite
|
Sign up to set email alerts
|

Fascaplysin Derivatives Are Potent Multitarget Agents against Alzheimer’s Disease: in Vitro and in Vivo Evidence

Abstract: Alzheimer’s disease (AD) is characterized by progressive neurodegeneration and impaired cognitive functions. Fascaplysin is a β-carboline alkaloid isolated from marine sponge Fascaplysinopsis bergquist in 1988. Previous studies have shown that fascaplysin might act on acetylcholinesterase and β-amyloid (Aβ) to produce anti-AD properties. In this study, a series of fascaplysin derivatives were synthesized. The cholinesterase inhibition activities, the neuronal protective effects, and the toxicities of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…The green fluorescence can be induced by fluorescein. Thus the FDA positive (green stained cells) and negative cells are live and dead cells, respectively (Pan et al, 2019). All the cells in Figure 1(E) were shown green, which indicates that the cultured cells are all live cells definitely.…”
Section: Resultsmentioning
confidence: 86%
“…The green fluorescence can be induced by fluorescein. Thus the FDA positive (green stained cells) and negative cells are live and dead cells, respectively (Pan et al, 2019). All the cells in Figure 1(E) were shown green, which indicates that the cultured cells are all live cells definitely.…”
Section: Resultsmentioning
confidence: 86%
“…Based on molecular modeling studies, 9-methylfascaplysin ( Figure 5 g), a fascaplysin derivative, was synthesized [ 60 , 61 ]. Docking analyses suggested that the binding to AChE active site differs from fascaplysin, which only binds to the peripheral anionic site.…”
Section: Marine Natural Productsmentioning
confidence: 99%
“…Docking analyses suggested that the binding to AChE active site differs from fascaplysin, which only binds to the peripheral anionic site. The referred derivative possibly binds also to the catalytic site residue leading to an enhanced AChE inhibitory activity [ 60 ].…”
Section: Marine Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations